RELATIONSHIP BETWEEN INFORMATION EXPOSURE AND KNOWLEDGE OF HIV/AIDS PREVENTION AMONG ADOLESCENT STUDENTS AT INSTITUT ILMU KESEHATAN PELAMONIA - Iismayanti Iismayanti; Edy Supardi; Tut Handayani; Amratul Jinan; Sultan Sultan (PT. Jurnal Center Indonesia Publisher, 2026)
Adolescents represent a high-risk group for HIV/AIDS infection due to limited knowledge of transmission mechanisms and appropriate prevention strategies. Health information exposure plays a critical role in shaping adequate knowledge as the foundation for preventive behavior. This study aims to determine the level of HIV/AIDS prevention knowledge among adolescent students and to analyze its association with health information exposure. A cross-sectional study was conducted among 189 students at Institut Ilmu Kesehatan Pelamonia in 2026, recruited via random sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test (α = 0.05). A total of 66% of respondents had sufficient knowledge of HIV/AIDS prevention; however, 48% had never been exposed to related health information. A significant association was found between health information exposure and knowledge level (p = 0.04; OR = 3.4; 95% CI: [complete]). Health information exposure is significantly associated with HIV/AIDS prevention knowledge among adolescent students. Health education institutions should strengthen structured and sustainable HIV/AIDS education programs to prepare students as future health professionals.